A study of boutique hotels in Singapore. - Lim, Grace Wenxin. (2010)
Boutique hotels have been a recent phenomenon in the hotel industry, especially in western countries. This trend has extended to Singapore. Nonetheless, there is contention regarding the vague definition of “boutique hotels” that may affect the authentic experience provided by the sector. The study addresses this issue and provides an overview of the boutique hotel sector in Singapore based on academic research conducted. The site visits and interviews revealed a general consensus amongst boutique hotel operators that boutique hotels are small with distinct architectural heritage or design that has a consistent theme reflected throughout the hotel. This view was echoed in the demand perspective from the surveys administered on local Singapore residents and tourists. However, they believe that general attributes such as location and quality of facilities also influenced their decision to stay at or patronise a boutique hotel. The recommendations, keeping in mind financial and resource considerations, tackled inadequacies highlighted in the survey such as the lack of awareness and knowledge about boutique hotels. The study concludes with a possible definition of a boutique hotel that it should possess a unique theme and outstanding, personalised service.